O curso de pedagogia: o que dizem os egressos sobre o seu lugar de professor alfabetizador - Mascarenhas, Selma Mendes Souza (2015)
Illiteracy in Brazil is an educational, social and political issue of great importance that creeps along our history, being the education of the alphabetizing teacher one of the factors that needs to be rethought, so that we can overcome it. In this perspective, we ask: how the current educational proposal of the course of pedagogy of UEFS has contributed to the training of literacy teachers? As teachers who are trained in that course feel about the task of teaching reading and writing? The proposition of the Pedagogy Program, according to the Resolution CNE / CP 01/2006, defines teaching as basis for the formation of the pedagogue, and this act primarily in childhood education and the early grades of elementary school, when the procurement processes reading and writing should be consolidated. In this sense, the objective of this work is known prospects of graduates teachers about the importance of the course of pedagogy of UEFS in their own training as literacy teachers. This qualitative study was used as methodological strategies documentary research on the norms of that course and curricular organization (national and local levels) and the semi-structured interviews with five teachers who worked in 1st year classes in 2014, discharged of the course Pedagogy of UEFS. During the research, we approach the different conceptions of literacy that permeate the history of education in Brazil and the various theoretical and methodological insights into the process of literacy looking for directly influence the pedagogical practice of literacy teacher, from theoretical as Ferreiro (2012) Soares (2002, 2004), Britto (2003), Kleiman (2007), Mortatti (2000) and Morais (2006). We also discuss some ideas about curriculum, using as support the contributions of Gimeno Sacristán (2000), Veiga-Neto (2002), Goodson (2007) and Silva (1999), passing then to discuss the historical construction of the curriculum of the course pedagogy in Brazil and its relation to the formation of literacy teachers, from authors like Saviani (2012), Libâneo (2006), Pimenta (1999), Brzezinski (2012) and Scheibe (2007).Finally, we analyze the course of pedagogy of UEFS from regulatory and organizational documents, as well as interviews with teachers, subject of this research, trying to understand the place and the importance of literacy in that course, with the contribution of theoretical above, and Tardif (2011), Brito (2006), Nóvoa (2009), Weisz (2003), among others. The research signaled, among other things, the persistent lack of identity of course, observed since its genesis, intending, at present, form the teacher to work in early childhood education classes and the early grades of elementary school as well as the specialist to act in the school field and not educational spaces, which promotes swelling and fragmentation of the curriculum, tending to the superficiality and precarious training and; the need for a review of the course of pedagogy of UEFS (as locus of teacher who teaches reading and writing), emphasizing that literacy needs to gain more space on your curriculum, considering the urgent need to qualify the training of teachers for reading and writing education, ensuring all learners the right to enter the world of literacy consciously and competently.